2018
DOI: 10.1093/mnras/sty664
|View full text |Cite
|
Sign up to set email alerts
|

Cylinders out of a top hat: counts-in-cells for projected densities

Abstract: Large deviation statistics is implemented to predict the statistics of cosmic densities in cylinders applicable to photometric surveys. It yields few percent accurate analytical predictions for the one-point probability distribution function (PDF) of densities in concentric or compensated cylinders; and also captures the density-dependence of their angular clustering (cylinder bias). All predictions are found to be in excellent agreement with the cosmological simulation Horizon Run 4 in the quasi-linear regime… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 69 publications
2
36
0
Order By: Relevance
“…The derivation of that value uses a spherical collapse approximation which may not be appro- priate for our cylindrical apertures. Substituting spherical with cylindrical collapse one arrives at ν = 7/5 (Uhlemann et al 2018c). In our situation we find both values for ν to give very similar values of b E 2 (as calculated from b L 1 and b L…”
Section: Halo Bias As a Function Of Mass And Consistency Among Bias M...mentioning
confidence: 99%
See 1 more Smart Citation
“…The derivation of that value uses a spherical collapse approximation which may not be appro- priate for our cylindrical apertures. Substituting spherical with cylindrical collapse one arrives at ν = 7/5 (Uhlemann et al 2018c). In our situation we find both values for ν to give very similar values of b E 2 (as calculated from b L 1 and b L…”
Section: Halo Bias As a Function Of Mass And Consistency Among Bias M...mentioning
confidence: 99%
“…the matter density field is typically incorporated through an Eulerian expansion of the conditional expectation value δ halo |δm (see e.g. Efstathiou 1995;Manera & Gaztañaga 2011;Clerkin et al 2017;Friedrich et al 2018;Gruen et al 2018;Salvador et al 2019;Repp & Szapudi 2020, with an exception found in Uhlemann et al 2018c). This is somewhat unnatural, because standard methods to model the matter density PDF are typically built around the symmetric collapse of a leading order (saddle-point) configuration of the density field (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…One way to circumvent this issue is presented in section 4 below by means of nulling. Note that this approach significantly outperforms a standard lognormal approximation for κ + κmin as shown quantitatively in appendix D. Additionally, our formalism can potentially be applied to jointly model the statistics of lensing convergence considered here and tracer densities in thick redshift slices described in Uhlemann et al (2018c), a situation where the log-normal approximation has been shown to fail.…”
Section: Weak-lensing Convergence Pdfsmentioning
confidence: 86%
“…In the spirit of previous work done involving the density filtered in spherical cells, the parametrisation of ζ(τ ) in ν is taken so as to reproduce the value of the tree-order skewness for cylindrical symmetry as computed with perturbation theory. We shall then take ν = 1.4 (Uhlemann et al 2018c). See Appendix B for more details.…”
Section: Cumulants In Cylinders From Theorymentioning
confidence: 99%
“…Perturbative methods [1,2,[19][20][21][22][23], and the large deviation statistics-formalism developed in Refs. [24,25] are better suited in such a situation. In terms of physical input, our formalism is quite similar to the stochastic numerical method developed in Refs.…”
Section: Introductionmentioning
confidence: 99%